Intracranial subarachnoid hemorrhage following cervical laminoplasty: a report of two cases. (2nd September 2018) - Kondo, Yuichi; Fushimi, Kazunari; Takasawa, Makoto; Kanamori, Shigeo; Miyagawa, Takaki; Kawashima, Kenji; Yokoyama, Kazutoshi; Akiyama, Haruhiko
ABSTRACT: Intracranial hemorrhage is a rare complication of spinal surgery. Case 1 was a 58-year-old man who underwent cervical laminoplasty. No apparent iatrogenic dural rupture or cerebrospinal fluid leakage was observed. An hour after the surgery, the patient had convulsions and became restless thereafter. CT revealed an intracranial subarachnoid hemorrhage (SAH). The patient recovered normal consciousness the next morning. Case 2 was a 68-year-old woman who underwent cervical laminoplasty without postoperative cerebrospinal fluid leakage. Six days after the surgery, the patient continued to complain of nausea and headache. By 13 days, the patient reported relief from her symptoms. There was no evidence of cerebral aneurysm, or vascular malformation in both cases. Patients undergoing cervical laminoplasty might be at risk for developing SAH. Careful attention to intraoperative neck positioning, strict monitoring and control of perioperative blood pressure, and complete dural repair are essential measures for preventing SAH.